Inflasi dan Realisasi Pembiayaan Kepemilikan Rumah pada Bank Umum Syariah di Indonesia: Peran Pandemi Covid-19 Sebagai Pemoderasi - Arifin, Muhammad; Amri, Khairul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to estimate the realization of home ownership financing at Islamic commercial banks in Indonesia. Yield rate, inflation, and the Covid-19 pandemic are operationalized as predictor variables. In addition, the pandemic is also positioned as a moderating variable between the financing and yield rate, and inflation. Using monthly data for the period June 2014-February 2021, the analytical model used is multiple regression and moderated regression analysis (MRA). The study found that the yield rate and inflation had a negative and significant effect on the financing of home ownership. In contrast, the COVID-19 pandemic has no effect on financing, but this pandemic weakens the negative effect of inflation on home ownership financing